ANALISIS LAHAN KRITIS DAN ARAHAAN PENGGUNAAN LAHAN PADA SUB DAERAH ALIRAN SUNGAI BINANGA LANTANG DI SULAWESI SELATAN - anita ruhama; sudirman numba; Saida Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
Land use does not the rules of soil and water conservation potentially lead to land causes of degradation that will eventually lead to critical land.  The impact ofthe existence of critical landis the decrease of soil fertility, lack of water resoucesin dryseasonandin rain season.  Critical land mapping is necessary to determine the right efforts in the management of upper course of Binanga Lantang Sub Watershed until not distrub ecosystem balanced.This study aims to identify the extent and distribution of critical land and formulate appropriate land use directions to suppress degraded land in Binanga Lantang Sub Watershed.  The method based on Forestry Departement P.4/V-SET/2013 by overlap method, scoring and weighting of each parameter.  The parameters used are map of vegetation class, productivity class map, class map slope, erosion class map and class map management. Reseach results show (1) Classification of critical land after land use direction Binanga Lantang Sub Watershed is very critically broad area 2870,38 ha, critically area 3541,11 ha, rather critically area 4962,34 ha, critical potential 3121,75 ha and not critically area 170,95 ha.  (2) critical land Binanga Lantang Sub Watershed to reach 43,72 percen of the total watershed area.  The entire production forest area is critical, the protected forest arund 50 percent of the area is in critical condition and other uses are only 20 percent of the area is in critical condition.  (3) One of the efforts that can be done to minimize the increase in land criticality is agroforestry and rehabilitation.